Interfacial microstructures and properties of hyper-eutectic Al–21Si / hypo-eutectic Al–7.5Si bimetallic material fabricated by liquid–liquid casting route - M. Ramadan; M. Ramadan; A. S. Alghamdi (Mechanical Sciences, 2020)
The bimetal casting process using the liquid–liquid technique was developed to produce a high-quality hyper-eutectic Al–21Si / hypo-eutectic Al–7.5Si alloy bimetal material. Microstructure and microhardness were investigated as a function of the time interval between pouring hypo-eutectic and hyper-eutectic alloys. A bimetal material was successfully fabricated using a liquid–liquid casting technique with a 10 s time interval in a permanent mould casting. A unique structure comprised of hyper-eutectic Al–21Si, hypo-eutectic Al–7.5Si and a eutectic interface of 70 µm thickness was obtained. This structure totally differs from that obtained using a higher time interval above 10 s that showed an imperfect interface bond due to the shrinkage cavity and formation of oxides. The hardness variation from the upper zone of 117.5 HV to the lower zone of 76 HV corresponded to the variation in Si and the content of other alloying elements. The proposed total solidification time control method is a promising approach for the successful fabrication of liquid–liquid bimetal material.